A Systematic and Integrated Review of Mobile-Based Technology to Promote Active Lifestyles in People With Type 2 Diabetes. (March 2017) - McMillan, Kathryn Anne; Kirk, Alison; Hewitt, Allan; MacRury, Sandra
Aim: The aim was to review studies examining the effectiveness, acceptability, and feasibility of mobile-based technology for promoting active lifestyles in people with type 2 diabetes (T2D). Background: Benefits of leading an active lifestyle following a diagnosis of T2D, including improved glycemic control, have been reported. Studies examining the specific use of mobile-based technologies to promote an active lifestyle in T2D have not previously been reviewed. Methods: Research studies examining effectiveness, feasibility or acceptability of mobile-based technology for active lifestyle promotion for T2D management were included (n = 9). The databases searched included PubMed, Medline, ScienceDirect, and ACM Digital Library (January 2005 to October 2015). Studies were categorized as (1) informing, (2) monitoring, (3) provoking, or (4) sustaining behavior change. Results: Technologies used included smartphone or tablet apps, diabetes personal digital assistant, continuous glucose monitor and accelerometer, pedometer, and a website delivered by a smartphone. No articles examined the effectiveness of mobile-based technology in monitoring health behaviors and behavior change. Four of the studies found mobile-based technology to be motivational and supportive for behavior change. The visual reinforcement was identified as motivational. The feasibility and acceptability of using mobile-based technology to provide sustained lifestyle change and the effectiveness of mobile-based technology in monitoring health behaviors and behavior change have not been investigated. No studies examined all 3 of the outcomes or focused decreasing the participants' sedentary behavior. Conclusions: Limited research has examined the feasibility, acceptability, and effectiveness of mobile-based technology to promote active lifestyles and subsequently good diabetes management in people with T2D.